Exploring the Relationship Between Innovative Work Behavior and Leadership: Moderating Effect of Locus of Control - Škudienė, Vida; Augutytė-Kvedaravičienė, Ieva; Demeško, Natalija; Suchockis, Anicetas (Organizations and Markets in Emerging Economies, 2018)
The topic of innovative work behavior has recently received an increased amount of attention due to a highly competitive, complex, and dynamic economic environment. This paper examines the effect of the leadership styles (transformational and transactional) on innovative work behavior. Moreover, the study explores moderation effects of internal and external locus of control in the relationship between transformational and transactional leadership and innovative work behavior. The findings indicate the importance of alignment of the transformational and transactional leadership styles with employees’ locus of control while aiming to transform organizational and individual resources into innovative outcomes. More specifically, the results show that contingent reward has stronger relationship with internal locus of control, whereas passive management by exception has stronger relation to external locus of control proving that enhancement of external employee motivation may boost employee innovative work behavior. Therefore, this study confirms that different leadership practices show specific linkage to certain locus of control type subordinates, meaning that their effectiveness can rise, if applied to this specific type of individuals. The research contributes to the existing knowledge of leadership styles and locus of control role in managing innovative work behavior and overall to the knowledge about how innovation can be managed in modern organizations.
Keywords: innovative work behavior; transformational leadership; transactional leadership; locus of control